Portal vein thrombosis and renal dysfunction: a national comparative study of liver transplant recipients for NAFLD versus alcoholic cirrhosis. (5th May 2021) - Molinari, Michele; Fernandez‐Carrillo, Carlos; Dai, Dongling; Dana, Jorgensen; Clemente‐Sanchez, Ana; Dharmayan, Stalin; Kaltenmeier, Christof; Liu, Hao; Behari, Jaideep; Rachakonda, Vikrant; Ganesh, Swaytha; Hughes, Christopher; et al.
Summary: The prevalence of portal vein thrombosis (PVT), renal dysfunction (RD), and simultaneous PVT/RD in liver transplantation (LT) is poorly understood. We analyzed the prevalence of PVT, RD, simultaneous PVT/RD, and the outcomes of adult recipients of LT for nonalcoholic fatty liver disease (NAFLD) and alcoholic liver disease (ALD) between 2006 and 2016 in the United States. We found that the prevalence of PVT (7.2% → 11.3%), RD (33.8% → 39.2%), and simultaneous PVT/RD (2.4% → 4.5%) has increased significantly over the study period (all P ‐values <0.05). NAFLD patients had a higher proportion of PVT (14.8% vs. 9.2%), RD (45.0% vs. 42.1%), and simultaneous PVT/RD (6.5% vs. 3.9%; all P ‐values <0.05). 90‐day mortality was 3.8%, 6.3%, 6.8%, and 9.8% for PVT(−)/RD(−), PVT(−)/RD(+), PVT(+)/RD(−), and PVT(+)/RD(+) recipients, respectively ( P < 0.01). 5‐year survival was 82.1%, 75.5%, 74.8%, and 71.1% for PVT(−)/RD(−), PVT(−)/RD(+), PVT(+)/RD(−), and PVT(+)/RD(+) recipients, respectively ( P < 0.05). In conclusion, the prevalence of PVT, RD, and simultaneous PVT/RD has increased among LT recipients, especially for those with NAFLD. The short‐ and long‐term outcomes of recipients with PVT, RD, and simultaneous PVT/RD were inferior to patients without those risk factors irrespective of their indication for LT. No differences in patient outcomes were found between ALD and NAFLD recipients after stratification by risk factors.